(untitled) (Research, Society and Development, 2021)
Brazil is a major producer of eggs and the State of São Paulo is the one that produces the most eggs in Brazil, with the Tupã region being the largest producer in the State with 55% of production and, in 2018 Bastos, the city with the largest production, contributed 36% of the São Paulo total. Thus, with these production volumes, it is possible to understand the importance of this productive sector, which demands technological innovations to guarantee permanence in the market and efficiency in production. The implementation of new technologies to automate the production of eggs does not always bring only positive results but requires adjustments to avoid losses during the production process. In this context, the problem arising from the automated egg transport systems, which can cause productive and financial losses for the farms, stands out. There are losses in the production line during automated transport from the warehouses to the final shipping process, where vibrations and impacts cause damage, as well as the times of exposure to the sun. Considering the scenario described, in this article the goal is based on prospecting the bibliography that demonstrated that there is already technology developed by peers to fully support the future technological development of an autonomous electronic system to be launched to the transport system, collecting data on obstacles, its position, and conditions of exposure to bad weather, which can be communicated with computers in the aviary management system and which can provide information in order to mitigate production losses, increasing the competitiveness and food security of the farms.